Aberrant angiogenesis in brain tissue in experimental Alzheimer’s disease - Ya. V. Gorina; Yu. K. Komleva; E. D. Osipova; A. V. Morgun; N. A. Malinovskaya; O. L. Lopatina; A. B. Salmina (Бюллетень сибирской медицины)
The aim was to study the molecular mechanisms of the violation of the structural and functional integrity ofthe blood-brain barrier in chronic neurodegeneration of the Alzheimer’s type associated with the development of cerebral angiopathy.Materials and methods. The transgenic model of Alzheimer’s disease is the B6SLJ-Tg line mice (APPSwFlLon,PSEN1 * M146L * L286V) 6799Vas group which includes 9 months aged males. The control group included C57BL / 6 x SJL mice, males aged 9 months.Results. The total length of the vessels in the area of the dentate gyrus is 2.5 times greater in transgenic animal models of Alzheimer’s disease than in animals of the control group (p < 0.01). The average diameter of blood vessels in all areas of the hippocampus is smaller compared with the control (p < 0.05). Transgenic modeling of neurodegeneration in the CA2 zone of the hippocampus increases the relative area of tissue with increased permeability of blood-brain barrier (BBB) (17.80 [9.15; 36.75]) compared to control (1.38 [0.04; 7.60]) at p < 0.05. A similar difference (p < 0.05) is also observed in the hippocampal area CA1. A tendency (p > 0.05) to decrease the number of CD31+ endothelial cells in the dentate gyrus of the hippocampus (21.52 [17.56; 24.50]) in animals of the experimental group compared with the control group (23.08[21.18; 29.84]) was detected. A similar situation is observed in the CA2 and CA3 areas of the hippocampus.Conclusion. Neurodegenerative changes in the hippocampus of animals with a transgenic AD model are associated with impaired microcirculation in the brain tissue as a result of a reduction in the diameter and branching of blood vessels, and damage and increased permeability of BBB.